Registros de eventos tafrogênicos intercalados tectonicamente no Complexo Pocrane, SE Minas Gerais - Tobias Maia Rabelo Fonte Boa (2017)
The internal domain of the Araçuaí-West Congo orogen comprises many varieties of rocks which were strong reworked during brasiliano orogenic cycle. In the vicinity of Pocrane and Durandé cities, western Minas Gerais, occurs metamafic, metasedimentary and metaultramaficrocks tectonically interlayered in the Rhyacian Pocrane complex. The geochronological and lithochemical study of two anphibolite lenses indicate two distinct magmatic events. The oldest, Calyminian event, with magmatic crystallization age at 1529 ± 37 Ma (U-Pb SHRIMP) and lithochemical signature of basaltic magmatism related to continental intraplate settings. The other event has zircon magmatic crystallization age at 1096 ± 20 Ma (U-Pb SHRIMP) and represent a Stenian event with lithochemical signature similar to mature magmatism of continental rift setting. The Calymmian event (ca. 1.5 Ga) correlates to the Espinhaço II basin stage and mafic dikes of the northern Espinhaço - Chapada Diamantina and Curaçá domains, while the Stenian episode (ca. 1.1 Ga) correlates to the Espinhaço III basin stage. We also present U-Pb data for 87 detrital zircon grains from a quartzite lens, the Córrego Ubá quartzite. Its age spectrum shows main peaks at 1176 ± 21 Ma (35%), 1371 ± 30 Ma (18%), 1536 ± 22 Ma (19%), 1803 ± 36 Ma (17%) and 1977 ± 38 Ma (12%), suggesting a Stenian (ca. 1176 Ma) maximum depositional age (although only one zircon with low discordance shows an age of 955 ± 66 Ma) which can be associated with the Early Tonian precursor basin of Araçuaí-West Congo orogen. In the region occur several small northeast-trending bodies hosting by orthogneisse basement and metasedimentary package which are intruded by granites. The geophysical survey performed in the Vista Alegre meta-ultramafic body indicates three relative shallow meta-ultramafic portions, insteadone deep continue body, interpreted as mega boudins aligned parallel to the regional foliation. These meta-ultramafic rocks are related to continuous crustal thinning, and integrates many others Meso and Neoproterozoic anorogenic magmatism events reported in southeast Brazil. The microscopic analyses show almost 2 distinct metamorphic events after emplacement. The first one seems to be related with collisional stage and the last one represents the thermal event during post-collisional event of the Araçuaí-Wets Congo orogen. Therefore, all the objects studied in this work testify the several unsuccessful fragmentation attempts that affected the long-lived São Francisco-Congo palaeocontinent.